النظام القضائي في الجزيرة العربية في العهد السعودي = The judicial system in the Arabian Peninsula during the Saudi era - Alsubhi, Amin Ali Ahmad; Mohamed, Hossam El-Din Ibrahim (Al-Hikmah Research and Publication Centre, 2024)
منذ نزل النبي ﷺ بالرسالة وأرشد الأمة إلى منابع الخير، كان من أولى اهتماماته ترسية العدل بين الناس وأطرهم على الحق، وحجب شر كل ذي شر عن الناس، حتى ينعموا بالأمن والسلامة في ظلال الدين الوارفة، لذلك ولّى النبي ﷺ قضاة في عهده يحكمون بين الناس ويفصلون في نزاعاتهم، وكان ديدن القضاة في الجزيرة العربية حتى عهد قريب الاجتهاد في الحكم في القضايا، ولم يلزموا بمذهب معين أو قول معين، وتكمن مشكلة المقال في اختلاف بيئات الجزيرة العربية سواء الجغرافية أو المعيشية والثقافية فكان لكل بيئة عادات وأعراف تحكمها ومن ذلك عاداتهم في نوعية وأساليب التقاضي، واستمر الحال على ذلك حتى بعد توحيد المملكة العربية السعودية في بداياتها، فالحجاز مثلاً ليس مثل نجد، ومعظمها لا تحقق العدالة والأمن للشعب، حتى تم توحيد النظام القضائي لاحقاً في جميع مناطق المملكة، وتظهر أهمية المقال في بيان وتوضيح المراحل التي مر بها القضاء في الجزيرة حتى انتهى إلى توحيده في هذا العهد السعودي، وإظهار الفروق الأدائية بين تلك المراحل، وهدف هذا المقال هو الإجابة على: كيف كان النظام القضائي في الجزيرة العربية قبل توحيد المملكة العربية السعودية؟، وكيف تطور النظام القضائي السعودي حتى وصل مرحلة التوحيد؟، وقد اتبع الباحث في مقاله المنهج الاستقرائي وذلك بجمع المعلومات من مضانها ومن ثم المنهج التحليلي من خلال تحليل هذه المعلومات وربط بعضها ببعض حتى نصل إلى النتائج المرجوة من المقال، وخلص المقال إلى أن توحيد القضاء من المتطلبات التي يحتّمها العصر الحديث، حيث انفتحت المجتمعات على بعضها، فيضطر القضاء إلى وضوح أدواته وبيان مواده وثباتها، وحتى لا يكون هناك ازدواج في الأحكام، أو تأخير للنظر في إصدارها. ***** Since the Prophet, (S.A.W), came with the message and guided the Ummah to the sources of goodness, one of his first concerns was to establish justice among the people, guide them to the truth, and withhold the evil from the people, so that they could enjoy security and safety under the protection of religion. Therefore, the Prophet, peace and blessings of Allah be upon him, appointed judges during his time to govern the people. They decide their disputes. Until recently, the practice of judges in the Arabian Peninsula was to exercise diligence in ruling on cases, and they were not bound by a specific doctrine or saying. The problem of the research lies in the differences in the environments of the Arabian Peninsula, whether geographical, living or cultural. Each environment has customs that govern it, including their customs in The quality and methods of litigation, and this remained the case even after the unification of the Kingdom of Saudi Arabia in its beginnings. Hijaz, for example, is not like Najd, and most of it did not achieve justice and security for the people, until the judicial system was later unified in all regions of the Kingdom. The importance of the research appears in stating and clarifying the stages that the judiciary passed in the peninsula until it ended with unification in this Saudi era, to show the functional differences between those stages. This article targets to answer: What was the judicial system in the Arabian Peninsula before the unification of the Kingdom of Saudi Arabia? And how did the Saudi judicial system develop until it reached the unification stage? In his article, the researcher followed the inductive approach by collecting information from its sources and then the analytical approach by analyzing this information and linking it together until we reach the desired results of the article. The article concluded that the unification of the judiciary is one of the requirements by the modern era, as societies have opened up on some of them, the judiciary is forced to clarify its tools and clarify its materials and their stability, so that there is no duplication of rulings, or delay in considering their issuance.